Activity of Albanian Emigration in the West towards the issue of Koso-vo and Metohija (1945–1969) - Vukadinović, Igor (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
After the Second World War, a large number of members of the fascist regime of the Kingdom of Albania found refuge in Italy, Turkey and the countries of Western Europe, where they continued to politically act. The leading political options in exile – Balli Kombetar, Zogists and pro-Italian National Independent Bloc, decided to cooperate with each other, so they have formed the Albanian National Committee in 1946. The turning point for the Albanian extreme emigration in the West is Operation Valuable, by which the United States and Great Britain sought to overthrow the communist regime of Enver Hoxha in Albania. Although the operation failed, strong ties were forged between US and British intelligence and Albanian nacionalist emigration, which were further intensified in the 1960s. Xhafer Deva, who was dedicated to act on the annexation of Kosovo and Metohija to Albania, immigrated to the United States in 1956 and estabileshd cooperation with the CIA. Albanian emigration in the West applied different methods in politics towards Kosovo and Metohija. Some organizations, such as Xhafer Deva's Third Prizren League, have focused on lobbying Western intelligence. The Bali Kombetar Independent, headquatered in Rome, paid particular attention to working with Albanian high school and student youth in Kosovo and Metohija. The Alliance of Kosovo, formed in 1949, was engaged in subtle methods of involving Albanian nationalists in Yugoslav state structures, the League of Communists of Yugoslavia, the Yugoslav People's Army, and educational and health institutions in Kosovo and Metohija. Albanian emigration was also involved in violent demonstrations in Kosovo and Metohija in 1968, and cooperated on this issue with the communist regime of Enver Hoxha in Albania.
Keywords: Albanian emigration; Kosovo and Metohijа; Xhafer Deva; Midhat Frasheri; Operation “Valuable”; Yugoslavia